A case study of improving milking cow performance and milking system performance with using a flow simulator. (9th June 2020) - Enokidani, Masafumi; Kawai, Kazuhiro; Shinozuka, Yasunori; Kurumisawa, Tomomi
Abstract: Efforts to improve dairy performance have been focused on increasing milk productivity of cows through improved feeding systems and genetic potential. However, methods for evaluating milking system performance based on milk productivity have not yet been established. Milking system performance was evaluated by measuring the claw vacuum at five flow rates (1.9–8.7 kg/min) produced using a flow simulator for a single eight‐swing milking parlor with a high‐line system. Based on these results, a double eight‐parallel milking parlor with a low‐line system was installed and tested. Farmers can take data obtained from evaluations of milking system performance into account for future management decisions, such as renewing the milking system. By renewing the milking system, average milking productivity, somatic cell linear score (LS) of bulk milk, and LS of each cow were significantly improved in the year after installing the new system ( p  < .01). In addition to checking conventional milking systems, this novel diagnostic method using a flow simulator can be used for checking new installations and also for proposing renovations.